2004
DOI: 10.1007/s00402-004-0728-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high tibial flexion osteotomy on cartilage pressure and joint kinematics: a biomechanical study in human cadaveric knees

Abstract: We conclude from these results that changes in tibial slope have a strong effect on cartilage pressure and kinematics of the knee. Therapeutically a flexion osteotomy may be used for decompression of the degenerated cartilage in the posterior part of the plateau, for example, after arthroscopic partial posterior meniscectomy. If a valgus osteotomy is combined with a flexion component of the proximal tibia, complex knee pathologies consisting of posteromedial cartilage damage and posterior and posterolateral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
252
1
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(281 citation statements)
references
References 12 publications
17
252
1
11
Order By: Relevance
“…The contact pressure at the cartilage surface was 4.2 MPa (Fig. 2d), which is in range of the reported data in the literature (Mononen et al 2011;Agneskirchner et al 2004;Meyer et al 2008;Marzo and Gurske-DePerio 2009;Morimoto et al 2009). …”
Section: Native Tissue Without Implantsupporting
confidence: 86%
“…The contact pressure at the cartilage surface was 4.2 MPa (Fig. 2d), which is in range of the reported data in the literature (Mononen et al 2011;Agneskirchner et al 2004;Meyer et al 2008;Marzo and Gurske-DePerio 2009;Morimoto et al 2009). …”
Section: Native Tissue Without Implantsupporting
confidence: 86%
“…Dejour and Bonnin reported for every 10°increase in PTS there is an anterior tibial shift of 6 mm in a monopedal stance test [13]. An experimental PTS increase (5°-20°) resulted in anterior (2.1 mm-4.6 mm) and superior (1.6 mm-4.1 mm) translation of the tibial plateau with respect to the femoral condyles [1]. Some authors presumed that with greater translation greater ligament loading occurred and placed the ACL at greater risk with an increased PTS [13,17,44].…”
Section: Introductionmentioning
confidence: 92%
“…It is defined by a tangent line to the respective tibial plateau and a line perpendicular to the longitudinal axis (LA) of the tibial bone that averages 10°(± 3°) on radiographs [9,13,16,19]. The measure reportedly influences knee kinematics [1,17] and ligament function [41,42,44]. Dejour and Bonnin reported for every 10°increase in PTS there is an anterior tibial shift of 6 mm in a monopedal stance test [13].…”
Section: Introductionmentioning
confidence: 99%
“…37 This decompression has been proposed as a possible treatment option for posterior cartilage damage. 37 However, no studies have shown the in vivo consequences of anterior contact pressure shifts on cartilage.…”
Section: Se = Standard Errormentioning
confidence: 99%